2021
DOI: 10.5114/aoms.2019.84487
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of waterpipe tobacco smoking among Polish youths

Abstract: IntroductionWaterpipe smoking is gaining popularity among the youth in Poland and is evaluated for the first time in this work. The authors address the social and demographic factors that motivate young people to smoke and attempt to determine which of them contribute to habit formation.Material and methodsThe data were collected among school and university students in Poland during a global survey on various forms of tobacco use. Multivariable regression models were applied for odds-ratio evaluation. The data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 60 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…In our study group, 11.6% of individuals were identified as potential problem drinkers. Zielińska-Danch tested the Polish population aged 15–25 and found that males were more than twice as likely as females to be current or ever waterpipe tobacco smokers, and those who reported waterpipe use were also more frequently street drugs and alcohol users [ 16 ]. Females reported seeking the help of a psychologist/psychiatrist more frequently than males ( Table VII A ), but sex was not significantly associated with the likelihood of ever visiting a psychologist/psychotherapist ( Table VII B ).…”
Section: Discussionmentioning
confidence: 99%
“…In our study group, 11.6% of individuals were identified as potential problem drinkers. Zielińska-Danch tested the Polish population aged 15–25 and found that males were more than twice as likely as females to be current or ever waterpipe tobacco smokers, and those who reported waterpipe use were also more frequently street drugs and alcohol users [ 16 ]. Females reported seeking the help of a psychologist/psychiatrist more frequently than males ( Table VII A ), but sex was not significantly associated with the likelihood of ever visiting a psychologist/psychotherapist ( Table VII B ).…”
Section: Discussionmentioning
confidence: 99%
“…According to estimates, about one-third of the adult Polish population smoke, with 36.9% of men and 24.4% of women [ 39 , 40 ] and over 35% of young people (15–25 years of age) declaring themselves regular smokers [ 40 ]. In our study, 28% of the CEs users reported nicotine use in different forms, with significantly higher prevalence in men than women, which is consistent with the general trend in Poland.…”
Section: Discussionmentioning
confidence: 99%